2005
DOI: 10.1159/000084017
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and β-Lactamase Production of Clinical Isolates of <i>Prevotella </i>and <i>Porphyromonas</i> Species

Abstract: Background: This study determined the β-lactamase production and the antimicrobial resistance of 72 Prevotella species and 48 Porphyromonas species isolated from different clinical specimens. Methods: All strains were identified using API 32 ID. The β-lactamase production was determined by nitrocefin disks. E test strips of benzylpenicillin, ampicillin + sulbactam, cefoxitin, clindamycin, metronidazole and imipenem were tested for each strain. Results: Nineteen Prevotella melaninogenica, 18 Prevotella intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 55 publications
(55 reference statements)
2
18
0
2
Order By: Relevance
“…The results of the present study showed that three antibiotics including amoxicillin/clavulanic acid, doxycycline and azithromycin had 100% activities against P. gingivalis which can provide alternative antibiotics to treat the patients whenever indicated. The fact that 12 % of the bacteria were resistant or intermediate resistant to amoxicillin but 100 % were sensitive to amoxicillin/clavulanic acid, indicates that resistance of P. gingivalis to β-lactam antibiotics are due to β-lactamase production (25,26). Low values of MIC 50 and MIC 90 of the three effective antibiotics were also noticed in this study, which could suggest that systemic antibiotic therapy may deliver adequate drug inside the infected teeth (27,28).…”
Section: Discussionsupporting
confidence: 49%
“…The results of the present study showed that three antibiotics including amoxicillin/clavulanic acid, doxycycline and azithromycin had 100% activities against P. gingivalis which can provide alternative antibiotics to treat the patients whenever indicated. The fact that 12 % of the bacteria were resistant or intermediate resistant to amoxicillin but 100 % were sensitive to amoxicillin/clavulanic acid, indicates that resistance of P. gingivalis to β-lactam antibiotics are due to β-lactamase production (25,26). Low values of MIC 50 and MIC 90 of the three effective antibiotics were also noticed in this study, which could suggest that systemic antibiotic therapy may deliver adequate drug inside the infected teeth (27,28).…”
Section: Discussionsupporting
confidence: 49%
“…This concentration is higher than the in vitro MIC 90 values (i.e. the minimum inhibitory concentration of an antimicrobial agent that inhibits the growth of 90% of susceptible isolates) shown in the in vitro susceptibility studies of oral bacteria referred to in our study [50][51][52][53][54][55]. Thus, 2 g/mL theoretically falls outside the normal distribution of MICs for each of the species under the current study.…”
Section: Discussionmentioning
confidence: 69%
“…The treatment of Prevotella spp. varies from β-lactamase to a combination of β-lactam-β-lactamase inhibitors, and carbapenems for more severe infections (7). The present study reports a brain abscess after chronic otitis media infection due to P. denticola, which is a rare cause of brain abscess.…”
Section: Introductionmentioning
confidence: 73%